Molybdenum isotope-based redox deviation driven by continental margin euxinia during the early Cambrian. (15th May 2022) - Qin, Zheng; Xu, Dongtao; Kendall, Brian; Zhang, Xingliang; Ou, Qiang; Wang, Xinqiang; Li, Jie; Liu, Jingao
Abstract: Oceanic redox changes may be a key environmental trigger for the "Cambrian explosion". However, a hypothesized predominantly oxygenated early Cambrian ocean, inferred from high sedimentary molybdenum (Mo) isotope ratios, conflicts with other evidence for euxinic continental margins. Here, we demonstrate that seawater Mo isotope ratios like those of today's predominantly well-oxygenated oceans can also occur in less oxygenated early Cambrian oceans. New and existing Mo isotope data from early Cambrian black shales in South China span a range of greater than 3‰, which can only be explained by multi-stage fractionation of Mo isotopes. The lowest Mo isotopes ratios likely reflect a Fe-Mn (oxyhydr)oxide shuttle that preferentially transferred the lighter Mo isotopes into weakly euxinic bottom waters where Fe-Mn (oxyhydr)oxide dissolution released isotopically light Mo that was then scavenged by organic matters and sulfide minerals. We use a novel isotope mass balance model to show that Fe-Mn (oxyhydr)oxide shuttle operating on euxinic continental margins would preferentially bury lighter-mass Mo isotopes to such an extent that early Cambrian seawater can become enriched in heavier Mo isotopes at levels comparable to modern seawater. Hence, widespread ocean oxygenation may not have occurred during the early Cambrian as previously thought. Based on this paradigm shift, reconsideration of sedimentary Mo isotope temporal trends suggests a stepwise and protracted oxidation of the oceans until the Late Devonian. Sporadic intervals with Mo isotope ratios spanning over 3‰ and often accompanied by dramatic change in biodiversity (e.g., Ediacaran-Cambrian and Permian-Triassic transitions) probably had euxinic continental margins. Links between fossil records and marine redox structures disclose the importance of spatiotemporal fluctuations in continental margin euxinia on biodiversity changes.